Cognitive techniques in clinical sexology - Кочарян, Гарнік Суренович (Psychological Counseling and Psychotherapy, 1970)
Different cognitive techniques for the treatment of patients with sexual dysfunctions are presented. Almost all of them were developed by the author of the article. Among them “false signal”, “decrease of the rank of significance of sexual disorders”, “psychotherapy with regard for the mechanism of projection”, “comparison by analogy”, “extension of consciousness”, “comparison by contrast”, and also a number of special techniques for correcting of the disease internal picture in males with different disorders of ejaculation.